2020
DOI: 10.23960/jpp.v10.i3.202005
|View full text |Cite
|
Sign up to set email alerts
|

Online Learning during Covid-19 Pandemic: Does It Run Well?

Abstract: Online Learning during Covid-19 Pandemic: Does it run well? Objectives: This article was aimed to identify the challenges that occur in the implementation of online learning during Covid-19 pandemic in several developing countries from teachers and students perspectives. Methods: We applied a systematic review of literature using search protocol based on the PRISMA recommendation statement. The initial step of the study was the formulation of the research problem, then search of relevant research results from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
(71 reference statements)
0
4
0
Order By: Relevance
“…Because most students lack technology skills, Nugroho (2020) found that converting the entire learning process to online classrooms is not successful. The findings of other studies revealed that students had difficulty with technology (Islam et al, 2015;Atmojo & Nugroho, 2020;Jhon et al, 2020;Alodwan, 2021). Some poor children in rural areas are less likely to use the Internet during the COVID-19 Pandemic (Ariyanti, 2020;Adnan & Anwar, 2020).…”
Section: Technical Challengesmentioning
confidence: 91%
“…Because most students lack technology skills, Nugroho (2020) found that converting the entire learning process to online classrooms is not successful. The findings of other studies revealed that students had difficulty with technology (Islam et al, 2015;Atmojo & Nugroho, 2020;Jhon et al, 2020;Alodwan, 2021). Some poor children in rural areas are less likely to use the Internet during the COVID-19 Pandemic (Ariyanti, 2020;Adnan & Anwar, 2020).…”
Section: Technical Challengesmentioning
confidence: 91%
“…According to John et al (2020), there was a lack of interaction and communication between teachers and students during the pandemic. Therefore, teachers claimed that limited physical interaction hampered good communication between teachers and students.…”
Section: Introductionmentioning
confidence: 99%
“…This requires teachers to make changes to their learning system (Yulia, 2020). The changes that occur also adjust to the situation and conditions of students during the Covid-19 pandemic (Jhon et al, 2020).…”
Section:  Introductionmentioning
confidence: 99%